Molecular prospective on the wheat grain development. (2nd January 2023) - Wang, Yiling; Sun, Genlou
Abstract: Wheat grain development is an important biological process to determine grain yield and quality, which is controlled by the interplay of genetic, epigenetic, and environmental factors. Wheat grain development has been extensively characterized at the phenotypic and genetic levels. The advent of innovative molecular technologies allows us to characterize genes, proteins, and regulatory factors involved in wheat grain development, which have enhanced our understanding of the wheat seed development process. However, wheat is an allohexaploid with a large genome size, the molecular mechanisms underlying the wheat grain development have not been well understood as those in diploids. Understanding grain development, and how it is regulated, is of fundamental importance for improving grain yield and quality through conventional breeding or genetic engineering. Herein, we review the current discoveries on the molecular mechanisms underlying wheat grain development. Notably, only a handful of genes that control wheat grain development have, thus far, been well characterized, their interplay underlying the grain development remains elusive. The synergistic network-integrated genomics and epigenetics underlying wheat grain development and how the subgenome divergence dynamically and precisely regulates wheat grain development are unknown.